2005
DOI: 10.1088/0957-0233/16/5/015
|View full text |Cite
|
Sign up to set email alerts
|

Development of slit-type pressure differentiator using an isothermal chamber

Abstract: Recently, measurement of the differentiated value of pressure has become necessary to realize precise control of pneumatic apparatuses. This paper proposes a pressure differentiator that contains a slit-type laminar flow element and an isothermal chamber. The underlying principle and the design method for the sensor are detailed. Then, simulations and experiments are conducted. The results verify the effectiveness of the proposed sensor and its potential in future applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Compared with differential calculating of the pressure, this scheme can obtain higher calculation accuracy with small data fluctuations, and can also directly measure the BPCR in real time. The measurement principle of the pressure differential gauge 17,18 is shown in Figure 2.…”
Section: Online Monitoring Implementation Scheme Of Bpcr In Brake Cha...mentioning
confidence: 99%
“…Compared with differential calculating of the pressure, this scheme can obtain higher calculation accuracy with small data fluctuations, and can also directly measure the BPCR in real time. The measurement principle of the pressure differential gauge 17,18 is shown in Figure 2.…”
Section: Online Monitoring Implementation Scheme Of Bpcr In Brake Cha...mentioning
confidence: 99%
“…A QFS is a differential pressure type flow sensor and its dynamic characteristics were calibrated using an "unsteady flow generator" in previous research [6]. The 'PD sensor' measures the pneumatic pressure differential with high precision and a quick response [7]. A schematic and photograph of the PD sensor used in this research are shown in Figs.…”
Section: Development Of a High Precisionmentioning
confidence: 99%
“…In this study, to solve this problem, we suggest the inlet flow rate control method with a sonic Venturi nozzle [12] and a high precise pressure control system [13,14] and apply this method to the unsteady mass flow generator. Moreover, we perform the experiments and uncertainty analysis and confirm the effective of the suggested method.…”
Section: Introductionmentioning
confidence: 99%
“…The laminar flow meter [16,17] and the PD sensor [13,14] were also developed in previous research. The laminar flow meter is a differential pressure type flow meter, whose dynamic characteristics are calibrated.…”
mentioning
confidence: 99%